Evaluation of a multicomponent vaccine in dogs - Chowdhury, Alak; Dighe, Dhananjay; Velhankar, Rajendra; Sarkar, Arunava; Nandi, Sani (International Journal of Biological Research, 2017)
The concept of combined viral and bacterial vaccines has been tried in cattle, canine and humans. Use of multicomponent vaccines has numerous advantages over individual vaccine. In this study, apparently healthy 8-9 weeks old 41 puppies were divided into 2 groups. 31 puppies (test group) were vaccinated subcutaneously with a commercially available multicomponent vaccine containing live attenuated strains of Canine Distemper virus, Canine Adenovirus type 2, Canine Parvo virus and Canine Parainfluenza virus and inactivated antigens of Leptospira canicola and Leptospira icterohemorrhagiae. 10 puppies were kept unvaccinated (control). Test group puppies were given a booster after 4 weeks of primary vaccination. Serum samples from both the groups were collected on 4 occasions (0th, 28th, 42nd and 90th day) and were tested for antibody titres against Canine Distemper virus and Canine Adenovirus type 2 by Serum Neutralization test, against Canine Parvovirus and Canine Parainfluenzavirus by Haemagglutination Inhibition test and against Leptospira canicola and L. icterohemorrhagiae by Microscopic Agglutination Test. A significant rise (P 0.5) in antibody titres was observed against all the antigens after vaccination. The control group did not show significant variation in the antibody titres. All puppies vaccinated subcutaneously with this vaccine did not evoke any local/ adverse reactions.